Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/pde.12786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a New Emollient‐Based Treatment on Skin Microflora Balance and Barrier Function in Children with Mild Atopic Dermatitis

Abstract: Background/ObjectivesThe use of emollients is widely recommended for the management of atopic dermatitis (AD), especially between flares. An imbalance of skin microflora is suspected of playing a key role in exacerbations of AD. Our aim was to evaluate the effect of a new emollient balm on clinical parameters (SCORing Atopic Dermatitis [SCORAD], xerosis, pruritus), skin barrier function (transepidermal water loss and loricrin, filaggrin, corneodesmosin, and involucrin expression], skin microflora biodiversity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 22 publications
(41 reference statements)
1
42
0
11
Order By: Relevance
“…Moreover, clinical studies were performed in infants, children, and adults with AD in order to assess the efficacy of an ES0-based cream in vivo; these results have been recently published and confirmed that an ES0-based cream applied twice daily decreased the SCORing Atopic Dermatitis53 and pruritus after 28 days of application 54. Furthermore, this ES0-based cream protected the skin from S. aureus proliferation and preserved microflora biodiversity.…”
Section: Resultsmentioning
confidence: 58%
“…Moreover, clinical studies were performed in infants, children, and adults with AD in order to assess the efficacy of an ES0-based cream in vivo; these results have been recently published and confirmed that an ES0-based cream applied twice daily decreased the SCORing Atopic Dermatitis53 and pruritus after 28 days of application 54. Furthermore, this ES0-based cream protected the skin from S. aureus proliferation and preserved microflora biodiversity.…”
Section: Resultsmentioning
confidence: 58%
“…These products may contain, for example, saponins, flavonoids and riboflavins from protein‐free oat plantlet extracts, or bacterial lysates from Aquaphilus dolomiae or Vitreoscilla filiformis . These lysates both improve AE lesions and influence the skin microbiome of AE patients . In vitro and clinical research data from different laboratories have provided some background information on molecular targets and possible mode of action of these active emollients ‘plus’ …”
Section: Basic Therapy Of Disturbed Skin Barrier Function and Emolliementioning
confidence: 99%
“…61 These lysates both improve AE lesions and influence the skin microbiome of AE patients. 62,63 In vitro and clinical research data from different laboratories have provided some background information on molecular targets and possible mode of action of these active emollients 'plus'. [64][65][66] Evidence of emollient efficacy Certain moisturizers could improve skin barrier function in AE and reduce skin susceptibility to irritants.…”
Section: Ingredients and Possible Risks Of Emollientsmentioning
confidence: 99%
“…Their data were regarded to be from an AD population. The age of the participants ranged from 2 months to 62 years and both sexes were included in 10 of the 11 studies . AD was clinically characterized by SCOring of Atopic Dermatitis (SCORAD) in eight of the studies; Eczema Area and Severity Index in one; and Rajka and Langeland in one .…”
Section: Resultsmentioning
confidence: 99%
“…The age of the participants ranged from 2 months to 62 years and both sexes were included in 10 of the 11 studies . AD was clinically characterized by SCOring of Atopic Dermatitis (SCORAD) in eight of the studies; Eczema Area and Severity Index in one; and Rajka and Langeland in one . Patients with mild AD were included in two studies; moderate AD in nine; and patients with severe AD in seven .…”
Section: Resultsmentioning
confidence: 99%